QUALITY OF LIFE OF MEDICAL AND DENTAL STUDENTS OF PESHAWAR - Ali, Omama; Salam, Zahwa; Saeed, Talia; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2018)
Objective: To find out the Quality of Life (QoL) of medical and dental students of Peshawar. Methodology: This cross-sectional study included students of public and private sector medical and dental colleges of Peshawar. To assess QoL, World Health Organization Quality of Life (WHOQoL-BREF) instrument was used. This instrument comprises of 26 items, which measure physical health, psychological health, social relationships and environment. Each of the 26 items was rated from 1-5 on a five-point scale. The analysis was carried out using SPSS v.20. Results: The mean age of the sample (n=883) was 20.7 +1.7 years with ma- jority of female students (n=629, 71.2%). The Cronbach's alpha reliability of WHOQoL-BREF in our study was 0.910. Medical students had significantly more impairment in the social relationship domain of QoL than dental students (p =.008). Male students had significantly better quality of life in the physical health domain of QoL than female students (p =.003). Similarly, students of private sector had better quality of health in physical health and environment domain of QoL as compared to students of public sector (p =.002 and .008, re- spectively). There was no significant difference between pre-clinical and clinical students regarding their quality of life. Conclusion: Students from dental colleges had higher scores in the domain of social relationship but female students had poor scores in the domain of phys- ical health. It was also observed that students from public sector colleges had higher mean scores in the domain of environment.